Search for bioactive compounds from medicinal plants used as antimalarials : the study of Momordica balsamina L. - Ramalhete, Cátia Beatriz Almeida, 1980- (2010)
Tese de doutoramento, Farmácia (Química Farmacêutica e Terapêutica), Universidade de Lisboa, Faculdade de Farmácia, 2010